Pelatihan Pembibitan Pohon (Multi Puspose Tree Species) MPTS Siswa SMA untuk Meningkatkan Kepedulian Terhadap Lingkungan - Alfia Dewi Fadwati , Alfia Dewi; Mondina, Resta Rene (Program Studi Kehutanan, Universitas Khairun, 2025)
The training activity on Multi-Purpose Tree Species (MPTS) tree seedling aimed to enhance the understanding and skills of students from SMA Negeri 9 Samarinda in environmentally friendly seedling techniques. This training was conducted to provide practical knowledge to students regarding seed sowing, seed scarification, and MPTS tree care techniques, which have significant benefits for both the environment and the economy. The methods used in this training included providing educational material on the importance of MPTS trees in supporting environmental sustainability, hands-on practice in seed sowing and scarification, and an environmental campaign through the creation of posters to encourage students to be more aware of reforestation. The results of the training indicated a significant improvement in students' understanding of the importance of reforestation and proper tree seedling techniques. Furthermore, the training successfully fostered awareness and concern for environmental preservation, as reflected in their enthusiasm for hands-on seedling practice and discussions on the long-term benefits of MPTS trees. This program also encouraged students to develop entrepreneurial ideas based on MPTS plants, which could support nature-based economies in the future. Thus, this training is expected to make a tangible contribution to environmental conservation efforts and increase ecological awareness among the younger generation.